Política curricular como política cultural: uma abordagem metodológica de pesquisa - Ozerina Victor de Oliveira; Denise de Souza Destro (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
Our objective is to discuss conceptions of curricular policy to characterise a methodological research approach that provides evidence of counterhegemonic processes in curriculum policies. We presuppose the centrality of culture in epistemological terms, the broadening of the political field and the non-binary spatial logic of post-colonial studies. Based on this exercise we define curricular policy as an historical process in which different protagonists, imbued with their cultural/social projects, produce tension around the production, flow and consolidation of meanings in the school curriculum, understood as a cultural policy. We suggest the transposition of the hegemonic methodological approach, that is, from the global/local perspective to the local/global perspective and consider it an error to centre on production or implementation, State or daily life in research on curricular policy. Finally, we point to questions that can guide studies within this perspective.